Pengembangan SIMPAS : Sistem Pendaftaran Pasien Online Sebagai Salah Satu Bentuk Layanan Prima Pada Unit Kesehatan - muhammad Sholeh (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
This study aims to develop a patient registration system that provides online outpatient registration services. With an online system the patient registration process can be done quickly, anywhere and anytime by prospective patients. Research methodology or information system development carried out in this research is to apply the concept of full water. In developing the SIMPAS system, the initial step is to conduct a system analysis, analysis, design, code and testing, implementation and maintenance. Before the process of making an application, it is preceded by a system design using a design tool that is UML and the results of the database implemented in the application have been normalized, so that the database designed has been minimized due to duplication of data. The results of the study resulted in the SIMPAS application developed with PHP programming and processed data stored in a MySQL database. The SIMPAS application provides one solution in the process of providing services to patients. The SIMPAS application can reduce queuing in the patient registration process. The registration process can be standardized at home through the online system and from the online registration can be used as evidence in the inspection process that will be carried out.